2006
DOI: 10.1111/j.1442-2042.2006.01308.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of recurrence after vesicovaginal fistula repair

Abstract: Purpose:We evaluate the prognostic factors of recurrence in patients after the surgical repair of vesicovaginal fistula. Materials and methods : From 1985: From to 2002 women with vesicovaginal fistula underwent late (>3 months) surgical repair. A multivariate analysis of the data was performed with the EPI-INFO software. All P-values were two-sided, with odds ratio and 95% confidence intervals. Results: A total number of 73 patients underwent 97 procedures with a mean rate of 1.38 procedures/patient. The ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 7 publications
0
29
0
4
Order By: Relevance
“…However, a lower proportion of medium/large fistulas were seen in patients with secondary repair (1/21 vs. 28/118). Strong evidence indicated that fistula size was significantly associated with fistula closure [14,16,17,21] . Therefore, smaller fistula size after prior repair may be one explanation of the comparable success rate on second repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a lower proportion of medium/large fistulas were seen in patients with secondary repair (1/21 vs. 28/118). Strong evidence indicated that fistula size was significantly associated with fistula closure [14,16,17,21] . Therefore, smaller fistula size after prior repair may be one explanation of the comparable success rate on second repair.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies indicated that fistula repair outcomes were determined by certain fistula characteristics, such as fistula site, fistula size and degree of perifistula scarring [14][15][16][17] . Ayed et al [14] demonstrated that multiple fistula, fistula size and type and obstetrical etiology were associated with recurrent fistulas. Ockrim et al [16] reported that failed repair was significantly more likely in large VVF.…”
mentioning
confidence: 99%
“…In our series success rate was higher (87.50%) in gynaecological fistula where it was 42.11% in obstetrical cases p = 0.03. Ayed M reported that obstetric fistula has lower success in repair and is a significant prognostic factor; the recurrence risk was threefold higher 20 .…”
Section: Discussionmentioning
confidence: 99%
“…20 But, as the rate of relapse is not high in cases of a single VVF <1cm following nonobstetrical reasons, some do not recommend interposition. 12,21,22 In particular, Goyal et al 12 reported that the success rate of the layered closure technique without omental interposition for small (<1 cm) VVFs was 97.5% using a transabdominal or transvaginal approach. Nevertheless, in all reported studies for laparoscopic or robotic repair of VVFs, the omental transposition was performed.…”
Section: Discussionmentioning
confidence: 99%